Probing the mechanisms of enhanced crystallisation of APS in the presence of ultrasound. Issue 19 (4th May 2022) - Birkin, Peter R.; Youngs, Jack J.; Truscott, Tadd T.; Martini, Silvana
Abstract : Both bubbles and associated mechanical forces, enhance crystallisation of a lipid sample through primary and secondary effects. Abstract : Understanding the origins of the enhancement of crystallisation of a lipid (all-purpose shortening, APS) through the application of ultrasound is a fundamental pre-requisite for the exploitation of this technique in a wider context. To this end, we show here a number of measurements designed to probe the mechanisms responsible for this effect. For example, we show how the type of bubble cluster, produced at the sound source, alters the bubble population and residency time. In addition, to probe the various contributions to the enhanced crystallisation rate, isolation of the cluster environment below the piston like emitter (PLE) used as the ultrasonic source was shown to reduce the enhancement observed, but did not remove it entirely. This implied that the exposure of the liquid to pressure shocks and the environment around the cluster has a positive effect on the crystallisation kinetics. In turn the addition of extra seed crystals and mechanical agitation also enhances the rate of crystallisation. Finally, the time at which ultrasonic irradiation of the fluid is applied is shown to alter the kinetics observed. These observations suggest that two components are important: large bubble populations and mechanical effects on pre-existing crystals. These findings suggest that maximising these effects could be an eloquent way to enhance and control the material characteristics of materials produced in this manner.